(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
The communicative approach has become one of the most effective methods of teaching English as a foreign language because it emphasizes meaningful communication rather than the memorization of grammatical rules. This article examines effective ways of developing the teaching of English prepositions to A2 level learners through communicative language teaching. At this stage, students are expected to use English confidently in familiar situations; however, many of them experience difficulties in selecting and applying appropriate prepositions in spoken and written communication. The article discusses the importance of integrating grammar instruction with real-life communication, interactive classroom activities, pair and group work, role-playing tasks, visual learning materials, and technology assisted instruction. Furthermore, it highlights practical teaching strategies that help learners improve grammatical accuracy while developing fluency and communicative competence. The study concludes that communicative language teaching enables learners to understand the practical functions of prepositions and use them naturally in everyday communication.